Steve S. answered • 03/29/14

Tutoring in Precalculus, Trig, and Differential Calculus

f(x) = -6g(x)-1

f(x) = -6(2/(2x-5))-1

f(x) = -12/(2x-5)-(2x-5)/(2x-5)

f(x) = (-12-(2x-5))/(2x-5)

f(x) = (-12-2x+5)/(2x-5)

f(x) = (-7-2x)/(2x-5)

f(x) = –(2x+7)/(2x-5) <== an answer

Divide by 2x-5:

2x+7 | 1

2x-5

––––

0+12

f(x) = –(1+12/(2x-5))

f(x) = –1–12/(2x-5) <== answer that’s simpler

because you can pick off the horizontal and vertical asymptotes: y = –1 and x = 5/2.

Also simpler to differentiate or integrate in later calculus course.

Stephen W.

03/29/14